The factors of acceptance and use of HRIS - Dani Safaâ; Faridi Mohamed (Technium Social Sciences Journal, 2020)
In a context of digital transformation where companies are seeking to integrate new collaboration technologies, the implementation of an HRIS remains necessary to acquire real decision-making tools, essential for better strategic positioning. The acceptance and use of HRIS depends on several factors that we will study through the different theories and models that deal in one way or another with the acceptance, use and success of a technology, which will allow managers and HR professionals a better use of the system and user satisfaction .